2008
DOI: 10.1007/s11414-008-9130-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Service Experiences, and Outcomes of Transition-Aged Youth in Systems of Care: Programmatic and Policy Implications

Abstract: This article examines data for 8,484 transition-aged youth (TAY) in different age groups who received services in 45 federally funded systems of care between 1997 and 2006. Data from the national evaluation of these systems of care were used to compare descriptive and clinical characteristics at intake of TAY aged 14-15, 16-17, and 18 years, and service use and outcomes of TAY aged 14-15 and 16-17 at 6 and 12 months after system of care intake. Few studies have examined outcomes of TAY. The large national eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 39 publications
2
50
1
Order By: Relevance
“…This could, in turn, increase the potential for the youths' disengagement. Although youth generally have been shown to see their teams as less productive than other team members (Walker and Schutte 2005), older youth may be relatively more satisfied with ''team functioning'' of their teams, given that wraparound teams for transitioning youth often incorporate instrumental supports in plans (Manteuffel et al 2008), and these supports are seen as particularly desirable by this population ). Thus, divergence across team members' reports with greater age would be expected to occur on the cohesion dimension, but less so on the functioning dimension.…”
Section: Perceptions Of Wraparound By Transitioning Youth Versus Othementioning
confidence: 99%
See 1 more Smart Citation
“…This could, in turn, increase the potential for the youths' disengagement. Although youth generally have been shown to see their teams as less productive than other team members (Walker and Schutte 2005), older youth may be relatively more satisfied with ''team functioning'' of their teams, given that wraparound teams for transitioning youth often incorporate instrumental supports in plans (Manteuffel et al 2008), and these supports are seen as particularly desirable by this population ). Thus, divergence across team members' reports with greater age would be expected to occur on the cohesion dimension, but less so on the functioning dimension.…”
Section: Perceptions Of Wraparound By Transitioning Youth Versus Othementioning
confidence: 99%
“…Some recent evidence on differences in service utilization among families of older and younger youth in SOCs provides evidence to support this proposition. For instance, in a large, national sample of youth in SOCs (Manteuffel et al 2008), families of older adolescents (i.e., 16-17 year-olds) were less likely to receive respite services than families of younger (i.e., 14-15 year-old) adolescents in the first 6 months of SOC enrollment. Notably, this pattern did not persist into the second 6 months of care, suggesting that perhaps initial expectations that such family-focused services would be less needed were corrected through experience with relatively higher strain found among caregivers of older youth.…”
Section: Implications Of Findings On Age Differences In Family Enviromentioning
confidence: 99%
“…This group of children and adults includes 46% of the US population who experience mental health problems at some point in their lives and 6% of the population who face chronic and persistent mental illnesses that often require long-term or intermittent care (68,69,80). Moreover, a large proportion of the children and adults who receive mental health services do not benefit from care (76,108). Their outcomes are poor because they receive services from providers who do not use effective treatments or because they encounter various barriers that interfere with the availability, responsiveness, or continuity of the services they seek (30).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, two articles have been published examining outcomes for children receiving services within federally-funded systems of care across the country. Manteuffel et al (2002) reported that children's behavioral and emotional problems significantly decreased after 2 years of treatment, while Manteuffel et al (2008) used the reliable change index to examine outcomes and found that an average of 36.4% of youth improved, 49.7% remained stable, and the remainder exhibited poorer outcomes.…”
mentioning
confidence: 99%